Digital Transformation of Resident Services: Quality and Satisfaction Analysis at Andalas Residence - Haryanti, Haryanti; Soraya, Riska; Indraddin, Indraddin; Sari, Reno Novita (Universitas Negeri Padang, 2025)
Resident services at Andalas Residence have been relying on traditional methods that often face obstacles such as delays in response, lack of transparency, and difficulties in data management. This article aims to analyze and develop a digital technology-based resident service satisfaction survey system using the waterfall method. This research was conducted by distributing questionnaires to 286 respondents of Andalas Residence residents. The data obtained was analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) statistical method. The results showed that the application of digital transformation not only improved the quality of service but also the overall efficiency of dormitory management.